WYKORZYSTANIE NARZĘDZI INFORMATYCZNYCH W PRACY Z LEKTURAMI NA POZIOMIE A1/A2, CZYLI JAK MOŻNA KSZTAŁTOWAĆ SPRAWNOŚĆ CZYTANIA ZE ZROZUMIENIEM W NAUCZANIU ZDALNYM - Gierzyńska, Marta (Neofilolog, 2021)
Refining reading comprehension skills is one of the basic tasks that students of foreign languages and their teachers face. Some of the texts offered in students’ books do not make pupils interested in the topic, motivated or encouraged enough to develop their reading comprehension ability. The reason is that these texts are compulsory students have to read them which thus makes the readings less interesting. Learning foreign languages essentially should be focused on their posterior use in extracurricular, personal and then occupational conditions. Since reading is necessary, then choosing simple books in a foreign language would be worth considering. Such texts may be perceived by the students differently from the compulsory readings in class. What is more, reading didactically adapted, longer literary texts and their proper reception will certainly be satisfying for the student. This article provides the reader with the examples of using simplified readings in the global and detailed text processing which, in turn, takes into account techniques such as pre-reading, while-reading and post-reading. Furthermore, the article presents the ideas of including Information and Communication Technologies in teaching which influences students’ engagement and allows the teacher to monitor their work.